Performance analysis of super capacitor integrated PV fed multistage converter with SMC controlled VSI for varying nonlinear load conditions - Pandey, Shruti; Dwivedi, Bharti; Tripathi, Anurag (International Journal of Engineering and Technology, 2018)
This work comprises of an MPPT (maximum power point tracking) controlled Photovoltaic (PV) source, in combination with a superca-pacitor, cascaded with a Sliding Mode Controlled (SMC) Inverter, which supplies varying nonlinear loads. The varying solar irradiation effects and its intermittency have been successfully managed by the boost converter controlled by MPPT and supercapacitor controlled by bidirectional converter. The bidirectional converter step down and step up the terminal voltage and provides the power flow in a bidirectional manner. The proposed model helps in obtaining the seamless action under changing irradiation and for varying load conditions. The performance of the SMC controlled Inverter, when compared with a PI controlled Inverter, has been found to be superior in terms of power quality and robustness of the supply system.
Keywords: Photo Voltaic; Bidirectional Converter; DC-DC Boost Converter; Maximum Power Point Tracking; Sliding Mode Control; Supercapacitor; Voltage Source Inverter.